(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Broad-spectrum antibiotics are widely used in intensive care units (ICUs) because of the severity of infections and the need for early empirical therapy. However, inappropriate and excessive use contributes to antimicrobial resistance (AMR), increased morbidity, prolonged hospitalization, and rising healthcare costs. Drug utilization evaluation (DUE) helps assess prescribing practices and supports rational antibiotic use. Aim: To evaluate the utilization pattern of broad-spectrum antibiotics and assess antimicrobial resistance trends among patients admitted to the ICU of a tertiary care hospital. Materials and Methods: A prospective observational study was conducted in the ICU of a tertiary care hospital from November 2017 to November 2018. A total of 200 adult patients (18–65 years) who received at least one broad-spectrum antibiotic were included. Data on demographics, clinical indications, antibiotic class, dose, duration, type of therapy (empirical or culture-guided), microbiological findings, and outcomes were collected using a structured case record form. Descriptive statistical analysis was performed. Results: Of the 200 patients, 62% were male, with a mean age of 49.6 ± 11.2 years. Sepsis (36%) was the leading cause of ICU admission. Third-generation cephalosporins (32%), carbapenems (26%), and beta-lactam/beta-lactamase inhibitor combinations (21%) were most commonly prescribed. Empirical therapy accounted for 70% of prescriptions. Culture positivity was observed in 58% of cases, predominantly gram-negative organisms. Klebsiella pneumoniae (34.5%) and Escherichia coli (27.6%) were the most frequent isolates. High resistance to cephalosporins and fluoroquinolones and emerging carbapenem resistance were noted. Conclusion: Extensive empirical use of broad-spectrum antibiotics and significant resistance trends highlight the urgent need for antimicrobial stewardship, culture-guided therapy, and continuous resistance surveillance in ICU settings.